(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The paper presents an attempt to introduce an integrated model for analysing dimensional relationships. The basis for the application of a unified approach in revealing, analysing and solving the dimensional chains is the fact that each element of the dimensional relationships in the product has a spatial expression. The practical side of the proposed unified model for the analysis of dimensional relationships is also presented. The essence of this model is that a single approach is applied to solve all dimensional chains, regardless of their spatial location. The model represents the dimensional chain by the coordinates of a sequence of basic points, the distances between which determine the components of the dimensional chain.